Re-articulation of Black Motherhood: Black Feminist Standpoint on Mothering in Girl, Woman, Other - Amin, Ammara; Aftab, Asma (Pakistan Languages and Humanities Review, 2025)
The research paper explores what it means to be a Black mother or daughter in the contemporary world through a black feminist study of different female characters, mostly mothers and daughters situated across multiple contexts and times in Evaristo’s Girl, Woman, Other. Patricia Collins’ ideas regarding Black women’s standpoint on mothering are employed to explore the narrative as a potential site of agency and self-actualization for Black women. The paper establishes that Evaristo’s fiction deterritorializes the White feminist discourse which has ignored the experiences of Black women and stereotyped Black mothers through controlling images of Black womanhood. By contextualizing Black feminist standpoint within Black motherhood, this article suggests that Girl, Woman, Other reconfigures Black motherhood, already problematized by racism and sexism, in a global flux of gender, binaries and multiculturality and thereby decentres and detrritorializes White feminism.